2004
DOI: 10.1210/en.2004-0212
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Progesterone Receptors A and B in the Mouse Ovary during the Estrous Cycle

Abstract: Progesterone plays a central role in the regulation of ovarian function. The progesterone receptor (PR) has been shown to be essential for ovulation because mice lacking PR fail to ovulate and are infertile. PR is expressed as two isoforms, PRA and PRB, which have been shown to have different functional activities. In this study, we investigated the cellular distribution of PRA and PRB in the ovaries and oviducts of cycling mice using immunohistochemistry with isoform-specific monoclonal antibodies. In the ova… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
52
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(59 citation statements)
references
References 49 publications
6
52
0
1
Order By: Relevance
“…Our laboratory has demonstrated that treatment with human chorionic gonadotropin (hCG), mimicking endogenous preovulatory luteinizing hormone surge, induces the levels of PR protein isoforms in periovulatory granulosa cells in mouse ovary (62). Similar observations have been made in ovaries from intact adult mice during the estrous cycle (19) and in humans (22). In addition, the developmental time course of PR mRNA and protein expression has been extensively studied in the uterus by use of either ovariectomized animals (a background devoid of endogenous steroid hormones) treated with selected steroid hormones (27,30,31,70) or intact adult rats during the estrous cycle (46).…”
mentioning
confidence: 68%
“…Our laboratory has demonstrated that treatment with human chorionic gonadotropin (hCG), mimicking endogenous preovulatory luteinizing hormone surge, induces the levels of PR protein isoforms in periovulatory granulosa cells in mouse ovary (62). Similar observations have been made in ovaries from intact adult mice during the estrous cycle (19) and in humans (22). In addition, the developmental time course of PR mRNA and protein expression has been extensively studied in the uterus by use of either ovariectomized animals (a background devoid of endogenous steroid hormones) treated with selected steroid hormones (27,30,31,70) or intact adult rats during the estrous cycle (46).…”
mentioning
confidence: 68%
“…[43][44][45] Our previous studies suggested that UCH-L1 and UCH-L3, despite their high sequence homology, 12 have distinct expression patterns and differential function in testis and epididymis. 9,11 Here we show that these two proteins have distinct distributions: UCH-L1 is exclusively expressed on the plasma membrane of oocytes and embryos, whereas UCH-L3 is diffusely expressed in the cytoplasm (Figures 1B and 2B).…”
Section: Discussionmentioning
confidence: 99%
“…There is some confusion about the relative amounts of each in the corpus luteum. In mice, some authors have found that granulosa cell PR A is higher than PR B but PR is lost during luteinisation (Shao et al 2003), and others have found PR B to be predominant in the granulosa cell and present in the corpus luteum (Gava et al 2004). In the primate corpus luteum, Western blotting suggested that the major PR variant is the B isoform .…”
Section: Discussionmentioning
confidence: 99%